Archaeometric Characterisation of Decorated Pottery from the Archaeological Site of Villa dei Quintili (Rome, Italy): Preliminary Study - Michela Ricca; Giuseppe Paladini; Natalia Rovella; Silvestro Antonio Ruffolo; Luciana Randazzo; Vincenza Crupi; Barbara Fazio; Domenico Majolino; Valentina Venuti; Giuliana Galli; Mauro Francesco La Russa (Geosciences, 2019)
This work focused on the study of decorated pottery dated back to the 16th century from the Roman archaeological site of Villa dei Quintili, a monumental complex located in the south-eastern part of Rome (Italy). A minero-petrographic and geochemical study was undertaken to analyse five archaeological samples in order to define textural features and raw materials used for their production, along with the chemical and physical composition of the superficial decorative glazed coatings. For this purpose, different analytical methods were used, such as polarising optical microscope (POM), X-ray diffraction (XRD), micro-Raman spectroscopy, X-Ray fluorescence (XRF), and electron microprobe analysis coupled with energy dispersive spectrometry (EMPA-EDS). The results of such a multidisciplinary approach allowed us to achieve important results crucial to recognise the shards as majolica of the Renaissance period, improving knowledge about manufacturing processes of these renowned painted ceramic artefacts.